Pengembangan Model Pembelajaran Islam Berbasis Teknologi untuk Generasi Milenial - Mardiah Astuti; Herlina Herlina; Alvin Choirul Wafi; Raja Naufal Nabhan; M. Raihan (Lembaga Pengembangan Kinerja Dosen, 2023)
Every industrial revolution will have an impact on every aspect of daily life, including Islamic education. Begin by mentioning the current industrial revolution, which is still going strong and will continue to negatively impact Islamic education, particularly media that promotes learning. This effect cannot be reversed. Every action has both positive and negative effects. There is always a way to maximize positive effects and minimize or eliminate negative ones.